Validity and reliability of an instrument assessing the associated factors for preventive behavior towards dengue - Ghafar, Noraini Abdul; Shah, Shamsul Azhar (International Journal Of Community Medicine And Public Health, 2017)
Background: Dengue is one of the most important vector-borne diseases in Malaysia. Government efforts alone are not sufficient in preventing the disease if people continue to allow the widespread mosquito breeding in their housing compound. Individual or community behavior is an important factor in the prevention of dengue. However, there is no standard instrument to measure the associated factors of dengue preventive behavior. This study commenced to validate and assess the reliability of a newly developed instrument for the constructs measuring factors associated with dengue preventive behavior. Methods: A total of 327 respondents involved in this pilot study, which is a preliminary study to a larger scale study. Exploratory factor analysis (EFA) was employed to explore underlying constructs of the latent variables. Results: From the EFA, 10 factors (knowledge regarding dengue, behavior toward dengue prevention, fear and awareness toward dengue, motivation to adopt preventive behavior, medical practices for dengue fever, cooperation in dengue prevention, perceived susceptibility of dengue, perceived severity of dengue, perceived benefit from practicing dengue preventive behavior, and perceived barrier toward dengue preventive behavior) emerged contributing 63.1 percent of the total variance with the reliability of 0.791. Conclusions: The questionnaire is valid and reliable to measure the associated factors of preventive behavior toward dengue.